KEADILAN DISTRIBUTIF SEBAGAI VARIABEL MODERATING DALAM HUBUNGAN PARTISIPASI ANGGARAN DAN KINERJA DINAS - Wahyudin Nor (InFestasi, 2011)
This present research examined the effects that participation in budget preparation and the performances of government offices in Palangka Raya. These offices that turned to be executive elements of local government, were directly involved in budget preparation and served as working unit providing public services. Distributive justice perception were treated as moderating variable of this research. Samples taken in the research, were involved government offices in Palangka Raya. Analysis units utilized were the heads of offices, since they were mostly involved in budget processing in the offices. Data were collected through questionnaires, out of 82 questionnaires sent, only 48 questionnaires could be processed. The empirical result using simple regression showed that budget participation significantly effect on performance of government offices in Palangka Raya. But empirically result using residual approach showed that a fit between budget participation with contingent factor (distributive justice) does not effect performance significantly.